Impact of Door-To-Balloon Time on Long-Term Mortality after Primary PCI - Khan, Muhammad Niaz; Ali Shah , Hamid; Ali , Nasir; Rashid Qureshi, Amir; Ullah , Abid; Muhammad Salman (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the impact of door-to-balloon (D2B) time on long-term mortality and adverse outcomes in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) at Hayatabad Medical Complex, Peshawar. Methodology: A prospective observational study was conducted from January 2022 to December 2022, including 320 STEMI patients. Patients were categorized into two groups based on D2B times: <90 minutes and ≥90 minutes. Data on demographics, symptom-to-door times, D2B times, and outcomes (mortality and major adverse cardiovascular events (MACE)) were collected. Statistical analysis was performed using appropriate tests, with a significance level of p<0.05. Results: The mean symptom-to-door time was 145.6 minutes, and the mean D2B time was 96.7 minutes. Patients treated within <90 minutes of D2B time had a survival rate of 91.3% compared to 73.4% in the ≥90-minute group (p<0.05). MACE occurred in 12.5% of patients, with a higher prevalence in those with delayed D2B times. Male patients constituted 62.5% of the cohort, and the mean age was 54.3 years. Conclusion: Shorter D2B times significantly improve survival and reduce adverse outcomes in STEMI patients. Adhering to the recommended <90 minutes for D2B is essential for optimizing clinical outcomes. Systemic changes to reduce delays are imperative for improving STEMI care.